The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0363546509360406
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Improves Activity-Induced Pain in Comparison With Pain at Rest in Middle-Aged Patients With Significant Cartilage Degeneration

Abstract: Anterior cruciate ligament reconstruction in middle-aged patients with significant cartilage degeneration is effective in reducing activity-induced pain and instability. Even though all patients had less than severe arthritic changes on preoperative radiographs, the pain at rest did not improve after ACL reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Trojani et al 62 reported that reconstruction can restore knee stability with good patient satisfaction but that it does not modify the pain pattern in patients with a prior medial meniscectomy with articular cartilage changes in the medial compartment and preoperative medial joint pain. Kim et al 32 examined older patients who had grade III or IV articular cartilage changes and an intact meniscus at the time of reconstruction and concluded that these patients had improvements in activityrelated knee pain and instability but not rest pain. In the present review, of 574 patients who had a meniscal injury, 38.2% (n = 208) had a medial meniscal tear and 21.9% (n = 119) had a lateral meniscal tear at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Trojani et al 62 reported that reconstruction can restore knee stability with good patient satisfaction but that it does not modify the pain pattern in patients with a prior medial meniscectomy with articular cartilage changes in the medial compartment and preoperative medial joint pain. Kim et al 32 examined older patients who had grade III or IV articular cartilage changes and an intact meniscus at the time of reconstruction and concluded that these patients had improvements in activityrelated knee pain and instability but not rest pain. In the present review, of 574 patients who had a meniscal injury, 38.2% (n = 208) had a medial meniscal tear and 21.9% (n = 119) had a lateral meniscal tear at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…12 Inclusion criteria were age 18–40 years, normal body weight (calculated body mass index between 19 and 25). Patients presenting with varus/valgus deviation of more than 5°, 13 revision surgery, posterior or collateral instabilities larger than grade I, as well as osteoarthritis larger than grade I were excluded. Additionally, patients with meniscus lesions requiring surgical intervention which would change the postoperative rehabilitation programme were not included.…”
Section: Methodsmentioning
confidence: 99%
“…With this, reconstructive surgery may protect against the further progression of osteoarthritis as suggested in primary reconstruction surgery. 29,35 In the entire group of 57 patients, the total period of laxity was moderately correlated with the symptom and ADL scores. The revision ACL reconstruction and primary ACL reconstruction groups did not differ significantly with respect to the total period of laxity, making this factor less probable as the cause of the differences found between the 2 groups.…”
Section: Revision Versus Primary Acl Reconstructionmentioning
confidence: 95%